The role of religion on sport anxiety among elite athletes in Malaysia: An exploratory study / Syazana Shahdan - Syazana , Shahdan (2019)
Anxiety is known to have an influence on psychological and physiological aspects of athletes especially when it becomes uncontrollable, and religion has been viewed with great potential in controlling anxiety levels. Hence, this study aimed to explore the role of religion on sport anxiety among elite athletes in Malaysia. It employed the Interpretative Phenomenological Analysis (IPA) approach in order to have a deeper understanding of the research topic. Seventeen elite athletes (10 males, 7 females, age range: 19-to-26 years old) with various sport background voluntarily participated in arranged interviews. There are four religious affiliations involved in this study: Islam, Buddhism, Christianity, and Hinduism. The study found six religious coping strategies and seven positive psychological effects of utilizing religion to cope with sport anxiety. Prayers was identified as the most popular strategy used and calmness was the most mentioned effect of religion when utilize to alleviate anxiety levels. The findings show that religion can play an important role as an effective coping strategy to deal with sport-related anxiety among athletes who believe in religion.